TYROSINE KINASE GENE POLYMORPHISMS ASSOCIATE WITH FRESH SEMEN QUALITY FROM DAIRY BULL FRIESIAN HOLSTEIN - & et al., Hernawati (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This research aims to identify polymorphisms in TEK genes to identify any related possibility to fresh semen quality of FH bull using the PCR method. A total of 14 samples of bull’s whole blood were collected and also the quality of each bull’s fresh semen. DNA amplification was carried out using primer Forward (TEK_F) 5'-TAGATTGTCGCTTGCCTGGG-3 'and Reverse (TEK_R) 5'-CCTGTGCCGACAGGTTTACT-3'. Analysis of the DNA sequence results was carried out using BioEdit and NCBI BLAST software. The results showed that of the 7 samples producing 262 bp and found polymorphisms in the TEK gene sequence in 23 gene bank databases. In the analysis of the relationship between the motility of individual spermatozoa with mutations, r count> r table (0.806> 0.754) or significance value 0.754) or significance level